The Application of Electrostatic Precipitator (ESP) as Pollutant Reduction in Ship (Research, Society and Development, 2019)
The burning process of fuel from the main engine in ships impacts on air and sea pollution. Afterward, in overcoming the air pollution from the result burning in industry usually use electronic precipitator (ESP) by using electric field to precipitate gas pollutant from burning result. Thus, the aim of this research is making the concept of ESP (Electrostatic Precipitator) which can be used to reduce pollutant from the result burning in the main engine. Afterward, this research is used experiment as its method. The results of this study shows that before using the ESP tool, the NO2 levels is 7.70 mg/Nm3, while after using ESP Nitrogen Oxide (NO2) levels dropped to 3.85 mg/Nm3. Before using the ESP, the data on emissions gas had SO2 levels of 72.3 mg/Nm3, while after using ESP the levels of Nitrogen Oxide (NO2) dropped to 39.6 mg/Nm3. The level of Nitrogen Oxide (NO2) in gas emissions drops to 50% while the level of Sulfur Dioxide (SO2) in emission gas drops to 45.2%.